Giant condylomata acuminata of Buschke-Lowenstein: Surgical method as effective treatment and Imiquimod as adjuvant therapy in an immunocompetent patient - Reis, Helena Lucia Barroso dos; Caldas, João Victor Jacomele; Feltz, Carolina Azevedo; Machado, Danielle de Oliveira; Rosa, Lucas Donateli; Neves, Marize de Freitas Santos; Boldrini, Neide Aparecida Tosato; Ferreira, Dennis de Carvalho; Filho, Antônio Chambo (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Giant condylomata acuminata, also known as Buschke-Lowenstein tumor is a rare form of tumor of the anogenital condylomata acuminata, which is a sexually transmitted infection (STI) caused by the human papillomavirus (HPV). Objective: To report a case of giant condylomata acuminata in an immunocompetent patient. Case report: The patient was referred to the Outpatient Clinic for Sexually Transmitted Infections and AIDS at a public hospital in the city of Vitória, Espírito Santo State, Brazil, reporting the onset of progressive growth verrucous lesions on the external genitalia for four months. The patient underwent surgical ablation, and giant condylomata diagnostic confirmation was obtained through histopathology. She was treated with 5% imiquimod cream in routine applications for eight consecutive weeks to avoid recurrence and was also vaccinated for HPV after the procedure. Conclusion: Surgery excision is the treatment of choice in extensive genital condylomata lesions to exclude malignancy. Imiquimod use as adjuvant therapy for reducing recurrence seems to be adequate.